The fifth risk - Lewis, Michael (Michael M.) (New York : W.W. Norton, 2018)
Presents a narrative account of the post-2016 election chaos that took over Washington to reveal how a small number of uninformed Trump appointees are triggering devastating world consequences.
Keywords: United States -- Politics and government -- 2017-; Administrative agencies -- United States -- Management; Government executives -- United States; Public administration -- United States; Civil service -- United State s